Electroactive composite for wound dressing - Gupta, Abhishek; Amerei Bozcheloei, Zahra; Ghofrani, Alireza; Keramati Nejad, Somayeh; Chakraborty, Prithviraj; Suresh Ambekar, Rushikesh; Barati, Elham (Journal of Composites and Compounds, 2022)
Skin tissue engineering and wound healing are two applications where conductive biomaterials based on metal compounds, conductive polymers, or piezoelectric polymers have great potential. This is because of their excellent antibacterial and antioxidant activities, similar conductivity to human skin, photothermal effect, and electrically controlled drug delivery. Wound healing can be accelerated by using conductive materials to stimulate the activity of electrically responsive cells. Electroactive wound dressings can be made by combining non-conductive polymers with conductive compounds, and this article focuses on current developments in this area. It is detailed how these electroactive dressings (conductive polymers, metal-based, and piezoelectric-based dressings) accelerate the healing process, and the properties of these electroactive dressings are examined. Furthermore, electrical stimulation techniques for accelerating wound healing are discussed. The possibility for electroactive wound dressings to be used in vivo to track the progress of wound healing is also mentioned, as are future development directions.